Origin of Analyte-Induced Porous Silicon Photoluminescence Quenching. Issue 9 (September 2017) - Reynard, Justin M.; Van Gorder, Nathan S.; Bright, Frank V.
We report on gaseous analyte-induced photoluminescence (PL) quenching of porous silicon, as-prepared (ap-pSi) and oxidized (ox-pSi). By using steady-state and emission wavelength-dependent time-resolved intensity luminescence measurements in concert with a global analysis scheme, we find that the analyte-induced quenching is best described by a three-component static quenching model. In the model, there are blue, green, and red emitters (associated with the nanocrystallite core and surface trap states) that each exhibit unique analyte-emitter association constants and these association constants are a consequence of differences in the pSi surface chemistries.